A cross-sectional study of appropriateness evaluation of anticoagulation therapy for inpatients with nonvalvular atrial fibrillation - Zheng, Xiao-Yuan; Feng, Guang-Wei; Guo, Jing; Xie, Fen; Li, Xia; Zhang, Ming-Zhu; Zhang, Xiu-Fen; Wu, Xiu-Feng; Ding, Yong-Juan (Frontiers in Pharmacology, 2023)
Background: Oral anticoagulants (OACs) are essential for stroke prevention in patients with nonvalvular atrial fibrillation (NVAF). However, the appropriateness of anticoagulation treatment in locally practice remains unclear. This study evaluated compliance with anticoagulation therapy concerning the guidelines and drug labels in patients with NVAF.Methods: Hospitalized patients diagnosed with NVAF between November 1, 2020, and December 31, 2021, were retrospectively enrolled. The appropriateness of anticoagulation regimens at discharge was evaluated based on a flowchart designed according to atrial fibrillation (AF) guidelines and medication labels. Furthermore, we explored factors potentially influencing the "no-use of OACs" using binary logistic regression and verified anticoagulation-related issues through a physician questionnaire.Results: A total of 536 patients were enrolled in this study, including 254 patients (47.4%) with inappropriate anticoagulation regimens. 112 patients (20.9%) were categorized as "underdosing-use of OACs," 134 (25%) who needed anticoagulation therapy were "no-use of OACs" and eight (1.5%) were "over-use of OACs." The results of a binary logistic regression analysis showed that paroxysmal AF (odds ratio [OR], 7.74; 95% confidence interval [CI], 4.57-13.10), increased blood creatinine levels (OR, 1.88; 95% CI, 1.11-3.16), hospitalized pacemaker implantation (OR, 6.76; 95% CI, 2.67-17.11), percutaneous coronary intervention (OR, 3.35; 95% CI,, and an increased HAS-BLED score (OR, 1.62; 95% CI, were associated with "no-use of OACs" in patients with NVAF who had indications for anticoagulation therapy.For patients with NVAF with severe renal dysfunction and paroxysmal AF, anticoagulation therapy was inadequate. The underdosing-use of OACs in patients with NVAF was frequently observed. We recommend an anticoagulation management team to tailor anticoagulation regimens to suit each patient's needs.